Perilaku Menulis Fanfiction oleh Penggemar Kpop di Wattpad - Nadya Syaharani; Adi Bayu Mahadian (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2017)
Wattpad is one of the sites and blogging applications that provide facilities for users to write and read, meaning that the users can write stories and also read stories created by other users. One of the postings made by the user is fanfiction which is the imagination of fans about idols especially Kpop idol in the form of writing. The purpose of the study is to understand the motivation and know the process of making fanfiction by Kpop fans who write fanfiction on Wattpad. The research method used is grounded theory in which the researcher tried to find data by online and offline interview and observation on 10 informants with criteria is Kpop fans who write fanfiction in Wattpad. The results showed that there was a motivation from inside and outside of Kpop fans and the process of making fanfiction consists of three stages: the creative process, the writing process and the editing and posting process.